The effect of xylitol chewing gums and candies on caries occurrence in children : a systematic review with special reference to caries level at study baseline - Pienihäkkinen, Kaisu (Springer Nature, 2025)
Purpose: A systematic review of published data was carried out to assess the caries-preventive effects of xylitol chewing gums and candies in children.
Methods: Electronic and hand searches were performed to find clinical studies on the effects of xylitol chewing gums and candies on dental caries in children (≤ 18 years). Prospective randomised or controlled clinical trials published before 2023 were included in the review.
Results: The initial search identified 365 titles to be evaluated. After applying inclusion and exclusion criteria, 15 articles with either fair or low quality were reviewed. Nine articles studied chewing gums, five candies, and one both of them. In the ten evaluated xylitol chewing gum studies xylitol consumption significantly reduced caries occurrence when compared with no treatment or a placebo polyol gum. The effect was clinically significant in studies with high or moderate caries level at study baseline. The results also suggested that the caries-reducing effect of xylitol gums may differ from sorbitol/polyol gums. In five of the six heterogenous xylitol candy studies, no caries-reducing effect was found independent of caries level. In addition to caries level, also the daily xylitol dose was a confounding factor.
Conclusion: The present findings suggest that the caries-reducing effect of adding xylitol chewing gum to the daily diet has been well demonstrated in children and adolescents with high or moderate caries level at study baseline. Xylitol gum use could benefit subjects with active incipient caries lesions on smooth tooth surfaces.